Effect of Ca-substitution on the Magnetic and Dielectric Properties of Mn-Zn Ferrites - Rahman, M. M.; Halder, P. K.; Ahmed, F.; Hossain, T.; Rahaman, M. (Journal of Scientific Research, 2012)
Spinel Mn-Zn ferrites with composition MnxZn0.4Ca0.6-2xFe2+xO4, where x = 0.10, 0.15, 0.20, 0.25 and 0.30 have been prepared by conventional ceramic technique sintered at 1300 °C for 4 hours. The influence of Ca-substitution on various properties of Mn-Zn ferrites have been studied in this work. Investigations were carried out by the measurements of Curie temperature, permeability, loss tangent, Q-factor, dielectric constant and AC resistivity of the samples. Curie temperature (Tc), the real part of initial permeability (µ´), loss tangent (tan ?), and AC resistivity have been found to be decreased while the Q-factor increases with the increase in Ca-content. The frequency characteristics of the dielectric constant and AC resistivity have been found to be decreased as the frequency increases. Maxwell-Wagner interfacial type of dielectric polarization was observed with the addition of Ca-content over the entire range of frequency considered. Keywords: Spinel ferrites; Sintering temperature; Initial permeability; Dielectric constant. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.9752 J. Sci. Res. 4 (2), 297-306 (2012)